A Perspective on Human Rights, the Economic Liberalization of Education Provision in Indonesia - Obi Pratama (Amal Insani Foundation, 2023)
Education is a fundamental right that every citizen has access to, as stated in the preamble of the Undang-Undang Dasar 1945, which is about the nation's intellectual life. The economic liberalization of education provision refers to the recent use of education as a new tool to profit from all angles. Those with lower income levels may notice the effects of economic liberalization in implementing this education because it becomes more challenging for them to obtain the best education. The objectives of this study are to identify the economic liberalization that has taken place in the implementation of education in Indonesia, identify the effects of this economic liberalization, and discover the economic liberalization that has taken place in education provision in Indonesia through its perspective of human rights. A single embedded case study and a descriptive qualitative methodology are used in this study. The study results indicate that diverse parties must promote instruction that adheres to Indonesian national standards. Disparities and prejudice against particular groups seeking an excellent education must be removed to guarantee that every student has equitable access to a high-quality education that will help them develop their potential and talents. As the highest authority, the government should carry out planned programs in line with the desired objectives by evaluating field data and monitoring connected parties' performance.